2014
DOI: 10.1002/2014tc003574
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cenozoic strike-slip tectonics on the evolution of the northern Levant Basin (offshore Lebanon)

Abstract: Sedimentary basins adjacent to plate boundaries contain key tectonic and stratigraphic elements to understand how stress is transmitted through plates. The Levant Basin is a place of choice to study such elements because it flanks the Levant Fracture System and the Africa/Anatolia boundary. This paper uses new high-quality 3-D seismic reflection data to unravel the tectonic evolution of the margin of this basin during the Cenozoic, the period corresponding to the formation of the Levant Fracture System, part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 84 publications
9
87
0
Order By: Relevance
“…Solely permeabilities and specific surface areas were adjusted for cross‐cutting lithologies which enables possible vertical fluid migration pathways at timing of presumed fault activity. According to Ghalayini et al (), most faults were active during or after deposition of Miocene sediments, which supports a simplistic representation in numerical models that neglects fault‐related deformation. However, the study could benefit from the use of new modeling tools which can account for more robust fault behavior (Woillez, Souque, Rudkiewicz, Willien, & Cornu, ).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Solely permeabilities and specific surface areas were adjusted for cross‐cutting lithologies which enables possible vertical fluid migration pathways at timing of presumed fault activity. According to Ghalayini et al (), most faults were active during or after deposition of Miocene sediments, which supports a simplistic representation in numerical models that neglects fault‐related deformation. However, the study could benefit from the use of new modeling tools which can account for more robust fault behavior (Woillez, Souque, Rudkiewicz, Willien, & Cornu, ).…”
Section: Discussionmentioning
confidence: 73%
“…Fluid flow calculations are based on a fully implicit generalised Darcy flow migration scheme which accounts for the main mechanisms driving fluid flow in petroleum system: (a) buoyancy; (b) pressure gradients; and (c) capillary forces. Since faults can play an important role in the Levant Basin, a care has been given to account for some representative fault systems compiled and digitalised after Ghalayini et al () (Table ). We utilised a simplified approach for an initial approximation of fault related fluid migration pattern.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An improved understanding of the geology of the Levant region has been acquired from interpretations of this data-set by academic and industrial research partners. The results of these studies include: (i) a new stratigraphic model for the Levant Basin based on seismic data, extensive fieldwork, and forward modelling (Hawie et al, 2013(Hawie et al, , 2014(Hawie et al, , 2015; (ii) a more detailed structural framework for the Levant Basin and margin based on new 3D seismic data interpretation and analogue modelling (Ghalayini et al, 2014(Ghalayini et al, , 2016(Ghalayini et al, , 2017; (iii) a thorough geochemical assessment of source rock potential supported by extensive sampling onshore and regional basin modelling, providing an updated evaluation of the hydrocarbon potential of Lebanon (Bou Daher et al, 2014; and (iv) an improved model of the crustal structure of the Levant Basin confirmed by deep seismic and gravity modelling (Inati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%